Genomic Epidemiology of Shiga Toxin-Producing Escherichia coli Isolated from the Livestock-Food-Human Interface in South America - Nicolás Galarce; Fernando Sánchez; Beatriz Escobar; Lisette Lapierre; Javiera Cornejo; Raúl Alegría-Morán; Víctor Neira; Víctor Martínez; Timothy Johnson; Danny Fuentes-Castillo; Elder Sano; Nilton Lincopan (Animals, 2021)
Shiga toxin-producing Escherichia coli (STEC) are zoonotic pathogens responsible for causing food-borne diseases in humans. While South America has the highest incidence of human STEC infections, information about the genomic characteristics of the circulating strains is scarce. The aim of this study was to analyze genomic data of STEC strains isolated in South America from cattle, beef, and humans; predicting the antibiotic resistome, serotypes, sequence types (STs), clonal complexes (CCs) and phylogenomic backgrounds. A total of 130 whole genome sequences of STEC strains were analyzed, where 39.2% were isolated from cattle, 36.9% from beef, and 23.8% from humans. The ST11 was the most predicted (20.8%) and included O-:H7 (10.8%) and O157:H7 (10%) serotypes. The successful expansion of non-O157 clones such as ST16/CC29-O111:H8 and ST21/CC29-O26:H11 is highlighted, suggesting multilateral trade and travel. Virulome analyses showed that the predominant stx subtype was stx2a (54.6%); most strains carried ehaA (96.2%), iha (91.5%) and lpfA (77.7%) genes. We present genomic data that can be used to support the surveillance of STEC strains circulating at the livestock-food-human interface in South America, in order to control the spread of critical clones “from farm to table”.